2007
DOI: 10.1111/j.1538-7836.2006.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII: recommended terms and abbreviations

Abstract: Blood coagulation factor XIII (FXIII) exists both in plasma and also in the cytoplasmic compartment of platelets, monocytes, their bone marrow precursors and monocyte-derived macrophages. FXIII present in the plasma is of tetrameric structure consisting of two potentially active A subunits and two carrier/inhibitory B subunits. In contrast, the cellular form of FXIII is a dimer of A subunits. Recombinant variants of the cellular form have also been produced [see review articles 1-4].The terminology and abbrevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…1 FXIII-A is present in platelets [22][23][24][25][26][27] in large quantities; a single platelet contains 60 6 10 fg, 28 making local platelet FXIII-A concentration around 150-fold greater than that in plasma. 29 Platelet FXIII-A, also known as cellular FXIII, 30 is largely stored in the cytoplasm 23,24 and, in contrast to FXIII-A 2 B 2 , can be nonproteolytically activated by Ca 21 alone. 31 Platelet-rich clots in vivo are much more resistant to lysis than whole blood clots.…”
Section: Introductionmentioning
confidence: 99%
“…1 FXIII-A is present in platelets [22][23][24][25][26][27] in large quantities; a single platelet contains 60 6 10 fg, 28 making local platelet FXIII-A concentration around 150-fold greater than that in plasma. 29 Platelet FXIII-A, also known as cellular FXIII, 30 is largely stored in the cytoplasm 23,24 and, in contrast to FXIII-A 2 B 2 , can be nonproteolytically activated by Ca 21 alone. 31 Platelet-rich clots in vivo are much more resistant to lysis than whole blood clots.…”
Section: Introductionmentioning
confidence: 99%
“…Because FXIIIA272829 plays an unambiguous role in the stabilization of the fibrin clot during wound healing and because thrombomodulin, an anticoagulant, functions in a complex with thrombin and is important for the degradation and lysis of fibrin after vascular repair, cells were also screened for the expression of FXIIIA and thrombomodulin. FXIIIA mRNA was expressed by monocytes, and proteomic analysis of highly purified platelets revealed that these cells also produce FXIIIA protein.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes have a direct and dual role in coagulation by producing important cofactors for FX (FV, FVIII and FXIIIA), but additional regulation is provided through the production of thrombomodulin, which destabilizes fibrin clots30, impairs platelet function27282930313233 and activates the anticoagulant protein C pathway. Furthermore, the observation that LPS can regulate coagulation factor production by monocytes shows that the system is dynamic and responds to local cues, further supporting the hypothesis that regulation of coagulation factor production is highly context dependent and much more complex than thought.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin structure is reinforced by activated factor XIII (FXIIIa) [21], which forms covalent bonds between the γ and α chains resulting in γ‐γ dimers and α polymers. To a chemist, transglutaminases such as FXIIIa catalyze ligation rather than cross‐linking [22].…”
Section: Intermediates In Fibrin Polymerizationmentioning
confidence: 99%